Pengembangan Buku Pop Up Pengenalan Rumah Ulu Ogan Sebagai Media Edukasi Bagi Anak Sekolah Dasar - Umi Karmini; Hestia Rachmat Nunciata Lubis; Heri Iswandi (Penerbit dan Percetakan, CV. Picmotiv, 2025)
Rumah Ulu Ogan is one of the traditional houses of South Sumatra that holds significant historical and cultural value. However, the lack of engaging educational media for elementary school children has led to a decline in knowledge about Rumah Ulu. This study aims to design an interactive pop-up book as an educational tool for first to third-grade students in Palembang, enabling them to better understand the shape, function, and uniqueness of Rumah Ulu Ogan. The design process includes literature review, observation, and analysis of the learning needs of young students. A pop-up book was chosen for its ability to offer a more engaging visual and sensory experience compared to conventional books. The outcome of this design is expected to enhance children’s interest in learning while effectively introducing local culture